Formulation and In -Vitro Evaluation of Metoclopramide Hydrochloride Chewable Tablets - B, Smitha; Kulkarni, Suresh V; Manjunath, K; Bhagawati, S.T. (Journal of Biomedical and Pharmaceutical Research, 2022)
The objective of the present research work was to develop a formulation of Metoclopramide HCl chewable tablets with efficacy and better palatability. Metoclopramide HCl belongs to the class of Anti-emetic which is used to treat nausea and vomiting. Metoclopramide HCl chewable tablets were prepared by the direct compression method. Chewable tablets were prepared and evaluated. The pre-formulation studies of FT-IR revealed that there was no significant interaction observed between the drug and excipients. Formulated chewable tablets were characterized for appearance, weight variation, hardness, friability, moisture content determination, drug content, in-vitro drug release studies and drug release kinetic studies. Formulation F3 released 98.167% drug at the end of 4th min better than other formulations and obeyed Korsmeyer peppa’s drug release kinetics. Formulation F3 could be considered as best formulation based on drug release profile, physical texture and other properties. Metoclopramide HCl chewable tablets could be serve as promising drug delivery dosage form for geriatric and pediatric patients with improved palatability.